Tractive performances of single grouser shoe affected by different soils with varied moisture contents. (May 2019) - Ge, Jun; Zhang, Dashan; Wang, Xiulun; Cao, Chengmao; Fang, Liangfei; Duan, Yunmeng
The objective of this study is to clarify the differences of tractive performances generated by the sandy loam-grouser system and the clay soil-grouser system. The tractive performances of the grouser/track shoes are widely researched by previous researchers. However, it is essential to illustrate the influences of the soil properties on the tractive performances of the grouser shoe. Sandy loam and clay soil were used as the test soils for investigating soil parameters in this study. Moisture contents of soil were from 7.5% to 27%, dry basis. Parameters of sandy loam were obtained through direct shear tests, penetration tests, bulk density, and moisture content measurements in laboratory. The grouser shoe was made of steel. Based on the prediction result of tractive performances, the clay soil will always be performed better than the sandy loam no matter which dimension was chosen for single grouser shoe. Based on the experimental results, the grouser height of the track should be 5 cm in order to provide enough traction force, if a tracked vehicle is operated on the environment of either clay soil or sandy loam.